Association Between Free Fatty Acid (FFA) and Insulin Resistance: The Role of Inflammation (Adiponectin and high sensivity C-reactive Protein/hs-CRP) and Stress Oxidative (Superoxide Dismutase/SOD) in Obese Non-Diabetic Individual - Indriyanti Rafi Sukmawati; Marsetio Donoseputro; Widjaja Lukito (The Indonesian Biomedical Journal, 2009)
BACKGROUND: Obesity is highly related to insulin resistance, therefore, the increased number of obesity is followed by the increased prevalence of type 2 Diabetes Melitus. Obesity is associated with increased of reactive oxygen species (ROS) in muscle, liver and endothelial cells. The increase of ROS would lead to insulin resistance (IR) and increased proinflamatory protein. FFA plays an important role in IR by inhibiting muscle glucose transport and oxidation via effects on serin/threonine phosphorylation of IRS-1. The aim of this study was discover the existence of SOD, hs-CRP and and adiponectin levels towards the occurrence of insulin resistance which was caused by elevated level of FFA and to discover the interaction between SOD, hs-CRP and adiponectin in non diabetic obese adult male.METHOD: This was observational study with cross sectional design. There were 65 obese male non diabetic subjects and 45 non obese male non diabetic subjects who met the criteria. In this study, measurements were done on body mass index (BMI), fasting glucose, insulin, adiponectin, hs-CRP and SOD. Obese was defined as BMI >25 kg/m2, normal weight was defined as BMI 18.5-23 kh/m2 and Insulin Resistance was defined as HOMA-IR >1.RESULT: This study showed that Hypoadiponectinemia condition, decreased SOD level and high level of hs-CRP is associated with insulin resistance in obese non diabetic subject. Adiponectin and SOD were correlated negatively with insulin resistance in obese non diabetic (Adiponectin, r=-0.455, p<0.001; SOD, r=-0.262, p=0.003), hs-CRP was positively correlated with insulin resistance in obese non diabetic (r=0.592, p<0.001). FFA levels was increased in obese insulin resistance compared with non obese non insulin resistance. The Odds Ratio of Adiponectin, hs-CRP and SOD in this study was analyzed by logistic binary. The OR for SOD 3.6 (p=0.001), hs-CRP 9.1 (p<0.001) and Adiponectin 7.2 (p<0.001).CONCLUSION: This study suggested that FFA levels  increased in obese insulin resistance as compared with non obese non insulin resistance. Hypoadiponectinemia, decreased SOD and elevated hs-CRP were associated with insulin resistance in obese non diabetic subjects.KEYWORDS: obesity, insulin resistance, FFA, SOD, hs-CRP, adiponectin